Environment, Social, and Governance Performance and Financial Performance With National Pension Fund Investment: Evidence From Korea - Son, Sungjin; Kim, Jootae (Frontiers in Psychology, 2022)
Sustainable management is a hot issue in the current business research, and is understood in three areas of environment, social and governance. This study attempts to examine the relationship between ESG management and financial performance and the role of socially responsible investment of National Pension Fund (NPF), Korea’s largest institutional investor. This study tries to provide evidence for the slack resource hypothesis by verifying whether companies with higher financial performance make more efforts to improve ESG performance. In addition, we try to validate whether NPF is expanding its investments in corporations with high economic performance and high ESG performance. Based on our analysis, Korean companies with good financial performance actively participate in ESG. When we compare the performance between 2019 and 2020, companies with high ESG performance increased regardless of financial performance level whereas companies with high financial performance and low ESG performance decreased. This represents that perception and attitude of Korean companies toward ESG management is evolving. NPF has the high investment ratio for firms having high ratio in both financial and ESG performance. NPF further invested in companies with high ESG performance, even if the financial performance is not decent. This paper provides the evidence that Korean companies' interest in ESG management as well as the behavior of socially responsible investment of NPF are rising.